2017
DOI: 10.1044/2016_jslhr-l-16-0292
|View full text |Cite
|
Sign up to set email alerts
|

Sign Language Echolalia in Deaf Children With Autism Spectrum Disorder

Abstract: Deaf children with ASD sometimes echo signs, just as hearing children with ASD sometimes echo words, and TD deaf children and those with ASD do so at similar stages of linguistic development, when comprehension is relatively low. The sign language modality might provide a powerful new framework for analyzing the purpose and function of echolalia in deaf children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Further, children who are DHH alone also do not exhibit the difficulties maintaining social relationships that are seen in children with ASD. Patterns of stereotyped movements and rigidity in schedules are also not characteristic of children who are DHH without ASD [40,96]. Finally, in addition, to language and communication differences noted in the language section below, Kellogg et al [89] found that children with ASD had delays in symbolic play not typically seen in children DHH without ASD and two of the three participating children in their study of children with DHH-ASD, lost skills over time.…”
Section: Assessment and Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, children who are DHH alone also do not exhibit the difficulties maintaining social relationships that are seen in children with ASD. Patterns of stereotyped movements and rigidity in schedules are also not characteristic of children who are DHH without ASD [40,96]. Finally, in addition, to language and communication differences noted in the language section below, Kellogg et al [89] found that children with ASD had delays in symbolic play not typically seen in children DHH without ASD and two of the three participating children in their study of children with DHH-ASD, lost skills over time.…”
Section: Assessment and Identificationmentioning
confidence: 99%
“…However, it is also thought that the diagnosis of ASD is often overlooked in the population of students who are DHH [25,88] and diagnosis is complicated by the lack of standardized assessment instruments for ASD that are appropriate for the DHH population, difficulties in audiological assessment, overlapping characteristics of ASD and DHH, and diagnostic overshadowing [25,27,28,30,40,88]. The literature base in DHH-ASD is limited but includes identification and assessment [28,30,31,89], social interaction and behavior [90][91][92][93], speech development [13,32,41], sign language [94][95][96], AAC [97], family supports [98,99], and teacher perceptions [34,100]. A search of the research revealed no research specific to literature skills and DHH-ASD, therefore, what is included in the literacy section below is extrapolated from the literature on ASD.…”
Section: D/deaf/hard Of Hearing With Autism Spectrum Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…There have been very few studies investigating ASD in deafness (Quinto-Pozo et al 2011 ; Hansen and Scott 2018 ). Studies of communication skills in deaf children with ASD have identified characteristics of their communication equivalent to those found in hearing children with ASD (Scawin 2003 ; Shield and Meier 2012 ; Szymanski et al 2012 ; Shield et al 2015 , 2016 , 2017 ). For example, confusing self and other in both gesture and use of pronouns occurs in hearing children with ASD (Lee et al 1994 ).…”
Section: Introductionmentioning
confidence: 99%